2017
DOI: 10.1016/j.bjid.2017.01.009
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence and risk factors for human papillomavirus infection among Chinese ethnic women in southern of Yunnan, China

Abstract: The prevalence and genotype distribution of HPV varied among ethnic women in urban and rural area of Yunnan Province.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

5
22
1
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 29 publications
(29 citation statements)
references
References 29 publications
5
22
1
1
Order By: Relevance
“…In the 50 to 59 years age group, HR and multiple HPV prevalence increased with age. These findings are consistent with those of previous studies in that there is no significant difference in HPV genotype distribution according to age . However, our study shown that the risk of HPV infection increases in women as the husband's age increases.…”
Section: Discussionsupporting
confidence: 93%
See 2 more Smart Citations
“…In the 50 to 59 years age group, HR and multiple HPV prevalence increased with age. These findings are consistent with those of previous studies in that there is no significant difference in HPV genotype distribution according to age . However, our study shown that the risk of HPV infection increases in women as the husband's age increases.…”
Section: Discussionsupporting
confidence: 93%
“…The prevalence and ethnic genotype distribution of HPV in China has been previously described among Naxi (11.9%), Tibetan (27.4%), Uyghur (7.3%), Dai (9.9%), Hani (21.1%), and Han (6.7–29.6%) women . In the present study, HPV prevalence rates among Han, Yi, and Bai women were 8.3%, 7.8%, and 7.5%, respectively.…”
Section: Discussionsupporting
confidence: 68%
See 1 more Smart Citation
“…Remarkably, it should be noted that HR-HPV infection rate decreased with increasing education level, the same result was demonstrated from study conducted in Yunnan Province, China [26]. The women with junior high school and below had limited knowledge about cervical cancer and its prevention.…”
Section: Discussionsupporting
confidence: 70%
“…Meanwhile, in Yunnan South China, the prevalence of HPV was the highest at age <29 years in women living in urban areas and age >50 years in women living in rural areas. (11) This finding is quite different compared to our result. Although both studies involving women living in urban areas, the highest HPV prevalence in our investigation is found in women aged 35-44 years old.…”
Section: Advances In Health Sciences Research Volume 22contrasting
confidence: 99%